Working in a multicultural world : a guide to developing intercultural competence - Nardon, Luciara, 1972- (Toronto ; Buffalo : University of Toronto Press, 2017)
Measurable, data driven outcomes are not the only indicators of success in todays multicultural and globalized workforce. How employees interact with their colleagues and customers is also a significant factor in their career development. Luciara Nardon draws on her extensive research and international experience to guide employees and managers through the ambiguous and uncertain waters of todays multicultural workplace. Each intercultural encounter is unique, involving different people, contexts, dynamics, and actions which general cultural protocols are unable to address. In Working in a Multicultural World, Nardon offers a comprehensive framework for understanding intercultural interactions and developing skills for successful intercultural situations. Numerous examples and exercises, including how to reconcile personal beliefs of equality with a hierarchical workplace and how to respond to perceived aggressiveness in business negotiations, enable employees and managers to embark on reflective processes that will springboard their intercultural competence. Working in a Multicultural World is an accessibly written and valuable resource for all professionals in todays workplace as well as students and travelers interested in intercultural relations.
Working in a multicultural world -- Building intercultural competence through reflection -- Situating intercultural interactions -- Understanding culture -- Understanding individual differences -- Understanding situations -- Managing feelings Communicating across cultures -- Moving forward.
Includes bibliographical references and index.
Keywords: Intercultural communication; Interpersonal communication; Communication in organizations; Work environment; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / International / General